Producción de conocimiento, zonas epistémicas y colonialismo académico (Ensayos) - Reyes Rodríguez, Alixon David (2024)
The aim of this paper is to analyze the relationship between knowledge production, the emergence and marking of zones of epistemic influence, and academic colonialism in the context of educational research in Latin America. To this end, we start from a classic documentary review considering the conception of these two fundamental categories, namely, zones of epistemic influence and academic or intellectual colonialism. This allows us to conclude by affirming that, in effect, the constitution of such zones accounts for the colonialism denounced in the academic context, which in turn, conditions the production of knowledge from educational research, perpetuating ways of accessing the understanding of the educational act from a Euro-Western episteme that ignores the social, cultural and political characteristics of Latin America. Hence, the ways of doing research in education continue perpetuating the ways of understanding Latin American education and subalternizing the production of knowledge in the field.